2002
DOI: 10.1007/s00244-002-1155-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Numerical Sediment Quality Targets for the St. Louis River Area of Concern

Abstract: Numerical sediment quality targets (SQTs) for the protection of sediment-dwelling organisms have been established for the St. Louis River Area of Concern (AOC), 1 of 42 current AOCs in the Great Lakes basin. The two types of SQTs were established primarily from consensus-based sediment quality guidelines. Level I SQTs are intended to identify contaminant concentrations below which harmful effects on sediment-dwelling organisms are unlikely to be observed. Level II SQTs are intended to identify contaminant conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Sediment quality guidelines have been used in a variety of ways. They are used in the management of dredged materials (Casado-Martinez et al 2006) and as sediment quality remediation targets (Crane et al 2002;Crane and MacDonald 2003). They are solely used or integrated as a line of evidence into environmental risk assessments to evaluate the potential for adverse effects on aquatic life (Chang et al 2004;Long et al 2006;Thompson et al 2005;Apitz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sediment quality guidelines have been used in a variety of ways. They are used in the management of dredged materials (Casado-Martinez et al 2006) and as sediment quality remediation targets (Crane et al 2002;Crane and MacDonald 2003). They are solely used or integrated as a line of evidence into environmental risk assessments to evaluate the potential for adverse effects on aquatic life (Chang et al 2004;Long et al 2006;Thompson et al 2005;Apitz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in a study conducted in the St. Louis River, USA. Crane et al [13] found that their data set contained few highly contaminated samples, which resulted in low toxicity efficiency and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical mixtures present in each sediment sample were addressed in three of the empirical approaches by normalizing each chemical to its respective SQG value and then summarizing the values as the mean quotient (e.g., mean ERMq, mean SQGQ1q, mean consensus MECq). The mean quotient values for empirical guidelines have been widely used by others [10,[13][14][15][16][17]21,22]. The data were normalized for the EqP for organics approach by calculating the toxic units represented by each chemical and then summarized by calculating the sum of the toxic units.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…These have been developed in an attempt to account for the potential effects of multiple contaminants (assuming simple additivity), as well as the magnitude of exceedance above relevant SQGs. Various SQGQ methods have been developed and tested for their ability to accurately predict toxicity (Burmaster et al, 1991;Hyland et al, 1999;Thompson et al, 1999;Bombardier and Blaise, 2000;MacDonald et al, 2000b;Fairey et al, 2001;Ingersoll et al, 2001Ingersoll et al, , 2002Linkov et al, 2001;Long et al, 2002;Birch and Taylor, 2002;Crane et al, 2002;Grapentine et al, 2002b;Hyland et al, 2003;Tannenbaum et al, 2003;Riba et al, 2003). Because the mSQGQs generate a single number for each sam ple or site, which integrates information on all contaminants considered, it is, like the index-based values described below, a valuable communication graphical toolsites can be ranked or maps can be contoured to illustrate relative chemical screening risk (see Figure 3).…”
Section: Sqg Summentioning
confidence: 99%